Optimization of a multi-reflection time-of-flight mass spectrometer with transaxial mirrors providing spatial and energy tof focusing - Shugayeva, Tilektes; Spivak-Lavrov, Igor; Baisanov, Orda; Amantayeva, Amangul (Eastern-European Journal of Enterprise Technologies, 2025)
This study explores a multi-reflection time-of-flight mass spectrometer (TOFMS) based on transaxial electrostatic mirrors providing spatial and energy time-of-flight focusing of the ion beam. Analysis of existing solutions reveals that spatial-energy time-of-flight focusing in compact TOFMSs is achieved using additional focusing elements, which complicates the design, limits resolution, and reduces sensitivity. This paper demonstrates that three-electrode transaxial mirrors enable simultaneous spatial and energy time-of-flight focusing of ions without the use of additional focusing elements. Monte Carlo simulation of the beam dynamics has made it possible to determine the trajectories and flight times of ions under various initial conditions. It was found that two closely spaced vertical focusing modes provide time-of-flight focusing of ions with a relative energy spread of . A mass resolution of 10,000 at half-maximum confirms the high efficiency of the proposed structure. The spatial distributions of the ion beam demonstrate stable focusing in the detector plane when modeling particles larger than 1000. The results are attributed to the features of transaxial geometry, which enables three-dimensional spatial and energy time-of-flight focusing. The practical significance of this work is the applicability of such multi-reflector mass analyzers in laboratory and space research where a combination of high resolution and instrument compactness is required